Dear Monica Lewinsky : a novel - Langbein, Julia (Art historian) (Doubleday, 2026)
"A novel about a middle aged court stenographer who must reexamine an ill-advised affair she had with a professor during the summer of the Monica Lewinsky scandal"-- Provided by publisher.